Electronically tunable floating resistor - Pawarangkoon, P.; Kiranon, W. (My University, 2004)
A new design for an electronically tunable floating resistor is proposed. The proposed circuit can be realized as a positive or negative resistor without changing the circuit topology, and can be tuned electronically. Simulation results are obtained to show adequate agreement with theory.